On the nucleolar size and density in human early granulocytic progenitors, myeloblasts - Smetana, K; Klamová, H; Mikulenková, D; Pluskalová, M; Hrkal, Z (European journal of histochemistry, 2006)
Human myeloblasts were studied in bone marrow of patients suffering from chronic phase of chronic myeloid leukaemia to provide more information on the nucleolar diameter in these early granulocytic progenitors. These cells are a convenient model for such study since the number of myeloblasts in diagnostic bone marrow smears of investigated patients is larger than in not-leukemic persons because of the increased granulopoiesis. The nucleolar diameter was measured in myeloblasts after various cytochemical procedures such as methods for visualisation of RNA, DNA and proteins of AgNORs using digitized images and image processing. The results clearly demonstrated that values of the nucleolar diameter depended on the procedures used for visualising nucleoli. It seems to be also clear that a close relationship exists between the diameter of nucleoli and their number since the larger the number of nucleoli per cell the smaller their mean size. However, one of multiple nucleoli present in the nucleus is usually significantly larger. Moreover, the possibility exists that the variability of nucleolar diameter of leukemic myeloblasts and thus the heterogeneity of these cells might depend on various stages of the cell cycle as supported by nucleolar measurements on aging leukemic myeloblasts (K 562 cells) in vitro. Since the staining density of small and large nucleoli did not differ substantially after staining for RNA, it seems to be likely that the nucleolar size is directly related to the total RNA content in myeloblasts. In addition, karyometry combined with RNA cytochemistry still appears to be an useful tool to study nucleoli at the single cell level.
Keywords: kultivované buňky; K562 Cells; prekurzorové buňky granulocytů; Granulocytes; buněčné jadérko; buňky K562; granulocyty; Cell Size; RNA; velikost buňky; Cells, Cultured; barvení a značení; Humans; chronická myeloidní leukemie; Staining and Labeling; Granulocyte Precursor Cells; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; hematopoetické kmenové buňky; Cell Nucleolus; Hematopoietic Stem Cells; lidé